Surface-treated steel sheet and its manufacturing method

JP7637617B2Active Publication Date: 2025-02-28TOYO KOHAN CO LTD
-1 Cites 0 Cited by

Patent Information

Application Number
JP2021517163
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-04-27
Filing Date
2020-04-27
Publication Date
2025-02-28
Estimated Expiration
2040-04-27
Patent Text Reader

Abstract

Provided is a surface-treated steel sheet comprising a steel sheet and a nickel-cobalt-iron diffusion layer formed as an outmost layer on the steel sheet, wherein the Co concentration gradient ∆PCo is 33 mass% / 0.1 µm or less in the region between depth position DCo_MAX and depth position DCo_15% when the Ni strength, Co strength, and Fe strength of the nickel-cobalt-iron diffusion layer are measured continuously in the depth direction from the surface side by means of radio frequency glow-discharge optical-emission spectrometry and the Ni concentration, Co concentration, and Fe concentration at each depth position of the nickel-cobalt-iron diffusion layer are obtained on the basis of the Ni strength, Co strength, and Fe strength, DCo_MAX being the depth position at which the Co concentration is largest, and DCo_15% being a depth position closer to the steel sheet side than depth position DCo_MAX is and at which the Co concentration is 15% of the largest value.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a surface-treated steel sheet and a method for producing the same. [Background technology]

[0002] In recent years, portable devices such as audio equipment and mobile phones have come to be used in a wide variety of fields, and primary batteries such as alkaline batteries, secondary batteries such as nickel-metal hydride batteries and lithium-ion batteries are widely used as power sources for these devices. These batteries are required to have higher performance, such as higher output and longer life, and the performance of the battery container, which is filled with power generating elements made of positive electrode active materials, negative electrode active materials, and other materials, is also required to be improved as an important component of the battery.

[0003] For example, Patent Document 1 discloses a battery container in which a specific nickel-cobalt alloy layer is formed on the outermost surface that will become the inner surface of the battery container, from the viewpoint of improving battery characteristics when used as a battery container. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2012 / 147843 Summary of the Invention [Problem to be solved by the invention]

[0005] However, when the battery container of Patent Document 1 is used as a battery container for a battery using a strong alkaline electrolyte, such as an alkaline battery or a nickel-metal hydride battery, there is a problem that the contact resistance value of the inner surface of the battery container in contact with the electrolyte increases over time, resulting in a deterioration of the battery characteristics. In response to this, there has been a demand for further improvement of the battery characteristics, such as suppression of the deterioration of the battery characteristics over time.

[0006] An object of the present invention is to provide a surface-treated steel sheet which, when used as a battery container for a battery using a strongly alkaline electrolyte, has excellent battery characteristics and is capable of suppressing deterioration of the battery characteristics even after aging. Another object of the present invention is to provide a method for producing such a surface-treated steel sheet. [Means for solving the problem]

[0007] As a result of intensive research by the present inventors to achieve the above object, in a surface-treated steel sheet having a nickel-cobalt-iron diffusion layer formed on a steel sheet as a layer on the outermost surface side, the Co concentration in the nickel-cobalt-iron diffusion layer, which is determined by measuring the surface-treated steel sheet by high-frequency glow discharge optical emission spectrometry, is determined as a Co concentration gradient ΔP Co The present invention has been completed based on the discovery that the above object can be achieved by controlling the amount of

[0008] That is, according to the present invention, there is provided a surface-treated steel sheet comprising a steel sheet and a nickel-cobalt-iron diffusion layer formed as an outermost layer on the steel sheet, the surface-treated steel sheet being provided with a surface-treated nickel-cobalt-iron diffusion layer, the surface-treated steel sheet being provided with a surface-treated nickel-cobalt-iron diffusion layer, the surface-treated nickel-cobalt-iron diffusion layer being provided with a surface-treated nickel-cobalt-iron diffusion layer, and the surface-treated nickel-cobalt-iron diffusion layer being provided with a surface-treated nickel-cobalt-iron diffusion layer. Co_MAX and the depth position D Co_MAX The depth position that is closer to the steel plate than the depth position where the Co concentration is 15% of the maximum value is defined as D Co_15% In this case, the depth position D Co_MAX From the depth position D Co_15% Co concentration gradient ΔP Co is 33 mass % / 0.1 μm or less.

[0009] In the surface-treated steel sheet of the present invention, the Ni intensity, Co intensity and Fe intensity are continuously measured from the surface side of the nickel-cobalt-iron diffusion layer in the depth direction by high-frequency glow discharge optical emission spectrometry, and the Ni concentration, Co concentration and Fe concentration at each depth position of the nickel-cobalt-iron diffusion layer are determined based on the Ni intensity, the Co intensity and the Fe intensity. The depth position at which the Ni concentration shows the maximum value is designated as D. Ni_MAX and the depth position D Ni_MAX The depth position that is closer to the steel plate than the depth position where the Ni concentration is 15% of the maximum value is defined as D Ni_15% In this case, the depth position D Ni_MAX From the depth position D Ni_15% Ni concentration gradient ΔP Ni is preferably 15 mass % / μm or more.

[0010] In the surface-treated steel sheet of the present invention, the Ni intensity, Co intensity and Fe intensity are continuously measured from the surface side of the nickel-cobalt-iron diffusion layer in the depth direction by high-frequency glow discharge optical emission spectrometry, and the Ni concentration, Co concentration and Fe concentration at each depth position of the nickel-cobalt-iron diffusion layer are determined based on the Ni intensity, the Co intensity and the Fe intensity. Among the depth positions in the nickel-cobalt-iron diffusion layer where the Ni intensity is 0.5% of the maximum value, the depth position located on the surface side is defined as D Ni_0.5% In this case, the depth position D Ni_0.5% Ni concentration P Ni (D Ni_0.5% ) is 70 mass% or less, and the Co concentration P Co (D Ni_0.5% ) is 5 mass% or more, and the Fe concentration P Fe (D Ni_0.5% ) is preferably 15 mass % or more. In the surface-treated steel sheet of the present invention, Ni_0.5% Fe concentration P Fe (D Ni_0.5% ) is preferably 30 mass % or more. In the surface-treated steel sheet of the present invention, Ni_0.5%Co concentration P Co (D Ni_0.5% ) is preferably 12 mass % or more.

[0011] In the surface-treated steel sheet of the present invention, the content of Co contained in the nickel-cobalt-iron diffusion layer is 0.2 g / m 2 More preferably, it is equal to or greater than this. In the surface-treated steel sheet of the present invention, the content of Ni contained in the nickel-cobalt-iron diffusion layer is 0.2 to 12.5 g / m 2 It is preferable that: In the surface-treated steel sheet of the present invention, the content of Ni contained in the nickel-cobalt-iron diffusion layer is 0.2 to 7.0 g / m 2 It is preferable that: In the surface-treated steel sheet of the present invention, the total content of Ni and Co contained in the nickel-cobalt-iron diffusion layer is 1.6 to 14.0 g / m 2 It is preferable that: In the surface-treated steel sheet of the present invention, the total content of Ni and Co contained in the nickel-cobalt-iron diffusion layer is 1.6 to 7.5 g / m 2 It is preferable that:

[0012] Moreover, the surface-treated steel sheet of the present invention preferably further comprises an iron-nickel diffusion layer between the steel sheet and the nickel-cobalt-iron diffusion layer. In the surface-treated steel sheet of the present invention, the total content of Ni contained in the nickel-cobalt-iron diffusion layer and the iron-nickel diffusion layer is 1.0 to 12.5 g / m 2 It is preferable that: In the surface-treated steel sheet of the present invention, the total content of Ni and Co contained in the nickel-cobalt-iron diffusion layer and the iron-nickel diffusion layer is 1.6 to 14.0 g / m 2 It is preferable that:

[0013] The present invention also provides a battery container made of any one of the above surface-treated steel sheets. According to the present invention, there is provided a battery comprising the above battery container.

[0014] Further, according to the present invention, there is provided a method for producing the above-mentioned surface-treated steel sheet, comprising the steps of: depositing a nickel-containing layer having a nickel content of 0.2 to 12.5 g / m on the steel sheet; 2 forming a nickel plating layer having a cobalt content of 0.2 to 5.0 g / m on the nickel plating layer; 2 and subjecting the steel sheet on which the nickel plating layer and the cobalt plating layer are formed to a heat treatment at a temperature of 450 to 900°C, thereby forming a Co concentration gradient ΔP Co and forming a nickel-cobalt-iron diffusion layer having a nickel content of 33 mass % or less and a thickness of 0.1 μm or less as the outermost layer. Effect of the Invention

[0015] According to the present invention, it is possible to provide a surface-treated steel sheet that has excellent battery characteristics when used as a battery container for a battery using a strongly alkaline electrolyte and that can suppress deterioration of the battery characteristics even after aging. Furthermore, according to the present invention, it is also possible to provide a method for manufacturing such a surface-treated steel sheet. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a perspective view showing one embodiment of a battery to which a surface-treated steel sheet according to the present invention is applied. [Diagram 2] FIG. 2 is a cross-sectional view taken along line II-II in FIG. [Diagram 3] FIG. 3 is an enlarged cross-sectional view of part III in FIG. 2, showing one embodiment of the surface-treated steel sheet according to the present invention. [Figure 4] FIG. 4 is a diagram for explaining a method for producing the surface-treated steel sheet shown in FIG. [Diagram 5] FIG. 5 is a graph for explaining the measurement by high frequency glow discharge optical emission spectrometry. [Figure 6] FIG. 6 is a graph for explaining a method for determining the Co concentration gradient ΔPCo and the Ni concentration gradient ΔPNi. [Figure 7] FIG. 7 is a cross-sectional view showing a second embodiment of the surface-treated steel sheet according to the present invention. [Figure 8] FIG. 8 is a graph showing the results of measurement of the surface-treated steel sheet of Example 2 using a high-frequency glow discharge optical emission analyzer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. The surface-treated steel sheet according to the present invention is processed into an outer shape according to the desired shape of a battery. The battery is not particularly limited, but examples thereof include alkaline batteries, which are primary batteries, nickel-hydrogen batteries, and lithium-ion batteries, which are secondary batteries, and the surface-treated steel sheet according to the present invention can be used as a member of the battery container of these batteries. In the following, an alkaline battery is given as an example of a battery using a strongly alkaline electrolyte, and the present invention will be described in an embodiment in which the surface-treated steel sheet according to the present invention is used for a positive electrode can constituting the battery container of the alkaline battery.

[0018] Fig. 1 is a perspective view showing one embodiment of an alkaline battery 2 to which a surface-treated steel sheet according to the present invention is applied, and Fig. 2 is a cross-sectional view taken along line II-II in Fig. 1. In the alkaline battery 2 of this example, a positive electrode mixture 23 and a negative electrode mixture 24 are filled in a bottomed cylindrical positive electrode can 21 with a separator 25 interposed therebetween, and a sealing body consisting of a negative electrode terminal 22, a current collector 26, and a gasket 27 is crimped to the inner surface side of the opening of the positive electrode can 21. A convex positive electrode terminal 211 is formed in the center of the bottom of the positive electrode can 21. An exterior 29 is attached to the positive electrode can 21 via an insulating ring 28 in order to provide insulation and improve design.

[0019] The positive electrode can 21 of the alkaline battery 2 shown in Fig. 1 is obtained by forming the surface-treated steel sheet according to the present invention by a deep drawing method, a drawing and ironing method (DI method), a drawing and stretching method (DTR method), or a method combining drawing, stretching and ironing, etc. Hereinafter, the configuration of the surface-treated steel sheet according to the present invention (surface-treated steel sheet 1) will be described with reference to Fig. 3.

[0020] FIG. 3 is an enlarged cross-sectional view of the portion III of the positive electrode can 21 shown in FIG. 2, and the upper side in the figure corresponds to the inner surface of the alkaline battery 2 in FIG. 1 (the surface in contact with the positive electrode mixture 23 of the alkaline battery 2). As shown in FIG. 3, the surface-treated steel sheet 1 of this embodiment is formed by forming a nickel-cobalt-iron diffusion layer 12 on a steel sheet 11 constituting the surface-treated steel sheet 1. The surface-treated steel sheet 1 of this embodiment only needs to have the nickel-cobalt-iron diffusion layer 12 formed on at least one surface of the steel sheet 11, specifically, on the surface that will become the inner surface of the alkaline battery 2 (the surface that will become the inner surface of the battery container). The nickel-cobalt-iron diffusion layer may also be formed on the surface that will become the outer surface (the surface that will become the outer surface of the battery container) and may be formed on both surfaces, but it is preferable that the nickel-iron diffusion layer and the nickel layer are formed on the outer surface in this order from the steel sheet side in terms of rust resistance during storage or use as a battery.

[0021] The surface-treated steel sheet 1 of this embodiment is a surface-treated steel sheet having a nickel-cobalt-iron diffusion layer 12 formed on a steel sheet 11 as a layer on the outermost surface side, For the surface-treated steel sheet 1, the Ni intensity, Co intensity, and Fe intensity were continuously measured from the surface side of the nickel-cobalt-iron diffusion layer 12 in the depth direction by high-frequency glow discharge optical emission spectrometry, and the Ni concentration, Co concentration, and Fe concentration at each depth position of the nickel-cobalt-iron diffusion layer 12 were determined based on the Ni intensity, the Co intensity, and the Fe intensity. The depth position where the Co concentration has the maximum value is D Co_MAX and the depth position D Co_MAX The depth position that is closer to the steel plate 11 than the depth position where the Co concentration is 15% of the maximum value is defined as D Co_15%In this case, the depth position D Co_MAX From the depth position D Co_15% Co concentration gradient ΔP Co is 33 mass% / 0.1 μm or less.

[0022] <Steel plate 11> The steel sheet 11 of this embodiment is not particularly limited as long as it has excellent formability, but for example, low carbon aluminum killed steel (carbon content 0.01 to 0.15% by weight), ultra-low carbon steel with a carbon content of less than 0.01% by weight, or non-aging ultra-low carbon steel obtained by adding Ti, Nb, or the like to ultra-low carbon steel can be used. In this embodiment, hot rolled sheets of these steels are pickled to remove surface scale (oxide film), then cold rolled, electrolytically cleaned, annealed, and temper rolled, or those that are cold rolled, electrolytically cleaned, and then temper rolled without annealing can also be used. In addition, from the viewpoint of productivity, it is preferable to use a continuous steel strip as the steel sheet 11.

[0023] The thickness of the steel sheet 11 may be appropriately selected depending on the application of the surface-treated steel sheet, and is not particularly limited, but is preferably 0.015 to 1.5 mm. In the case of a steel sheet (carbon steel or stainless steel) for batteries such as alkaline batteries and coin batteries, 0.15 to 0.6 mm is preferable, and in particular, 0.15 to 0.5 mm is preferable for a steel sheet for alkaline battery cans. On the other hand, for applications requiring light weight and flexibility, a foil shape of 0.015 mm to 0.1 mm is preferable.

[0024] <Nickel-cobalt-iron diffusion layer 12> The surface-treated steel sheet 1 of this embodiment includes a nickel-cobalt-iron diffusion layer 12 on a steel sheet 11. In this embodiment, the nickel-cobalt-iron diffusion layer 12 can be formed, for example, by forming a nickel plating layer 13 and a cobalt layer 14 in this order on the surface of the steel sheet 11, as shown in Fig. 4, and then performing a heat treatment to thermally diffuse the iron, nickel, and cobalt contained in the steel sheet and each layer, thereby obtaining the nickel-cobalt-iron diffusion layer 12. However, the method for forming the nickel-cobalt-iron diffusion layer 12 is not particularly limited to this method.

[0025] The nickel-cobalt-iron diffusion layer 12 of the surface-treated steel sheet 1 of this embodiment has a Co concentration change rate, i.e., a Co concentration gradient ΔP Co However, it is controlled within a specific range. That is, for the surface-treated steel sheet 1, Ni intensity, Co intensity, and Fe intensity were continuously measured in the depth direction from the surface side of the nickel-cobalt-iron diffusion layer 12 toward the steel sheet 11 under predetermined measurement conditions by high-frequency glow discharge optical emission spectrometry, and the Ni concentration, Co concentration, and Fe concentration at each depth position of the nickel-cobalt-iron diffusion layer 12 were determined based on the obtained Ni intensity, Co intensity, and Fe intensity. The depth position at which the Co concentration showed the maximum value was designated as D Co_MAX At the depth position D Co_MAX The depth position on the steel plate 11 side of the specimen and where the Co concentration is 15% of the maximum value is defined as D Co_15% In this case, the depth position D Co_MAX From the depth position D Co_15% Co concentration gradient ΔP Co However, it is controlled to 33 mass % / 0.1 μm or less.

[0026] Here, the Co concentration gradient ΔP Co The method of determining will be described with reference to FIG. 5(A), FIG. 5(B) and FIG. 6(A).

[0027] First, in order to set the measurement conditions when performing the measurement by radio frequency glow discharge optical emission spectrometry, a sample for adjusting the measurement conditions (a sample in which a nickel plating layer and a cobalt plating layer are formed in this order on a steel sheet) is prepared. Then, for the prepared sample for adjusting the measurement conditions, measurements are performed from the surface of the cobalt plating layer toward the steel sheet by a radio frequency glow discharge optical emission spectrometry device under conditions such that the maximum values ​​of the obtained Ni intensity, Co intensity, and Fe intensity (i.e., Ni intensity in the area where Ni is detected simply in the nickel plating layer, Co intensity in the area where Co is detected simply in the cobalt plating layer, and Fe intensity in the area where Fe is detected simply in the steel sheet) are approximately equal to each other. An example of the measurement results is shown in FIG. 5(A). In FIG. 5(A), the vertical axis indicates the intensity, and the horizontal axis indicates the etching depth measured in the depth direction while sputtering with Ar plasma from the surface of the surface-treated steel sheet 1 by a radio frequency glow discharge optical emission spectrometry device. As a method for adjusting the maximum values ​​of the Ni intensity, Co intensity, and Fe intensity to be equivalent to each other, a method of adjusting the voltage (HV) of the photomultiplier tube channel of the high-frequency glow discharge optical emission spectrometer for each element to be measured can be used.

[0028] Here, since nickel, cobalt and iron have roughly the same sputtering rate with Ar plasma, when each of the individual materials nickel, cobalt and iron is measured with a high-frequency glow discharge optical emission spectrometer, the amount of etching of each individual material will be roughly the same if the sputtering conditions (Ar gas pressure (unit: Pa) and output (unit: W)) are the same. Therefore, the amount of nickel etched that contributes to the measured Ni intensity, the amount of cobalt etched that contributes to the measured Co intensity, and the amount of iron etched that contributes to the measured Fe intensity will all be roughly the same.

[0029] Therefore, as shown in Fig. 5(A), by performing measurements using a high frequency glow discharge optical emission spectrometer under conditions where the maximum values ​​of the Ni intensity, Co intensity, and Fe intensity are approximately equal (in the example shown in Fig. 5(A), the intensity ratio obtained from the Ni intensity, Co intensity, and Fe intensity can be used directly as the mass ratio of Ni, Co, and Fe. For example, the ratio of Fe intensity to the total of Ni intensity, Co intensity, and Fe intensity can be used directly as the ratio of Fe mass to the total of Ni mass, Co mass, and Fe mass (Fe content (mass %)), and the same applies to Ni and Co. In this embodiment, the measurement conditions (voltage of the photomultiplier channel) using the high-frequency glow discharge optical emission analyzer are set in advance in this manner, and measurements are performed on the surface-treated steel sheet 1 under the set conditions. From the obtained Ni intensity, Co intensity and Fe intensity, the Ni content, Co content and Fe content relative to the total content of nickel, cobalt and iron at each depth position (depth position determined from the measurement time when measuring while sputtering) can be determined.

[0030] Regarding the measurement conditions using a high-frequency glow discharge optical emission analyzer, in the example shown in FIG. 5(A), the maximum values ​​of Ni intensity, Co intensity, and Fe intensity were adjusted to about 2.0 V, but the maximum value of the intensity is not limited to 2.0 V and can be any value. However, if the value is too low, the sensitivity of the measurement may decrease, and if the value is too high, the intensity obtained may saturate and an accurate value may not be obtained. Therefore, the HV is set so that a sufficient maximum intensity that does not become saturated or insufficient in sensitivity is obtained when the sample for adjusting the measurement conditions is measured. Usually, the range is ±1.0 V of the value measured at the recommended or standard HV of the measurement device. In the measurement of the examples described later, the maximum Ni intensity measured when the HV of Ni was set to 630 V was used. The thickness of each layer of the nickel plating layer and the cobalt plating layer of the sample for adjusting the measurement conditions is preferably 0.2 to 1.0 μm in order to obtain sufficient strength.

[0031] Then, after setting the measurement conditions of the high-frequency glow discharge optical emission analyzer by the method shown in FIG. 5(A), the surface-treated steel sheet 1 of this embodiment is measured under those measurement conditions, whereby the Ni content, Co content and Fe content in the nickel-cobalt-iron diffusion layer 12 can be determined.

[0032] Here, Fig. 5(B) is a graph in which Ni intensity, Co intensity and Fe intensity were continuously measured in the depth direction from the surface side of the nickel-cobalt-iron diffusion layer 12 toward the steel sheet 11 of the surface-treated steel sheet 1 of Example 1 described later by high-frequency glow discharge optical emission spectrometry under the above measurement conditions. Also, Fig. 6(A) is a graph showing the relationship between the etching depth and the Co concentration created based on the Co intensity data shown in Fig. 5(B), and Fig. 6(B) is a graph showing the relationship between the etching depth and the Ni concentration created based on the Ni intensity data shown in Fig. 5(B). Note that Fig. 5(A), Fig. 5(B), Fig. 6(A) and Fig. 6(B) are all graphs in which the horizontal axis represents the etching depth, and the etching depth can be determined from the measurement conditions (including the sputtering conditions) of the high-frequency glow discharge optical emission spectrometry and the sputtering time. In other words, for a steel sheet on which a nickel plating layer has been formed that has not been subjected to heat treatment and whose adhesion amount is clear, the etching rate is calculated from the sputtering time from the start of etching to the time when the strength reaches 10% of the maximum Fe strength and from the adhesion amount, and by using the same measurement conditions as at that time, the etching depth can be determined based on the sputtering time of the surface-treated steel sheet.

[0033] Since the graph shown in FIG. 5(B) shows the results measured under the above measurement conditions, the intensity ratio calculated from the Ni intensity, Co intensity, and Fe intensity can be used as the mass ratio of Ni, Co, and Fe, and the mass ratio of Ni, Co, and Fe, i.e., Ni concentration, Co concentration, and Fe concentration, can be calculated at each depth position in the nickel-cobalt-iron diffusion layer 12. Specifically, for example, the ratio (%) of Ni intensity to the total of Ni intensity, Co intensity, and Fe intensity (Ni intensity / (Ni intensity+Co intensity+Fe intensity)×100) can be used as the mass ratio of Ni, i.e., Ni concentration. The mass ratio of Co and the mass ratio of Fe can also be calculated in the same way, and these can be used as the Co concentration and Fe concentration. FIG. 6(A) is a graph showing the Co concentration (i.e., the mass ratio of Co to the total of Ni mass, Co mass, and Fe mass) calculated in this way at each depth position in the nickel-cobalt-iron diffusion layer 12.

[0034] In this embodiment, as shown in FIG. 6A, the Co concentration reaches a maximum value at point F Co_MAX The depth position corresponding to Co_MAX Let F be such a point. Co_MAX The concentration is at point F Co_MAX (Depth position D Co_MAX ) The point F that shows 15% of the maximum Co concentration shown in Co_15% The depth position corresponding to Co_15% In this case, the depth position D Co_MAX From the depth position D Co_15% Co concentration gradient ΔP Co When calculating the Co concentration gradient ΔP Co That is, referring to FIG. 6(A), the thickness of the crystalline silicon layer at the depth position D Co_MAX (Point F Co_MAX ) The Co concentration at the depth position D Co_15% (Point F Co_15%The Co concentration at the depth position D is about 6.75 mass%. Co_MAX (Point F Co_MAX ) is near the etching depth of 0.2 μm, and the depth position D Co_15% (Point F Co_15% ) is near the etching depth of 0.7 μm, and the Co concentration gradient ΔP Co This gives a calculation result of 7.8 mass% / 0.1 μm.

[0035] That is, in the embodiment 1 shown in FIG. 6(A), the depth position D Co_MAX (Point F Co_MAX ) is the vertex, and the depth position D Co_15% (Point F Co_15% 6(A), the Co concentration decreases at a rate of 7.8 mass % for every 0.1 μm. Since the rate of decrease in the Co concentration is not constant, as shown in FIG. 6(A), in this embodiment, the Co concentration is decreased at a rate of 7.8 mass % for every 0.1 μm. Co_MAX and depth position D Co_15% The rate of change in the Co concentration measured based on the Co concentrations at the two points and is called the Co concentration gradient ΔP Co In other words, "Co concentration gradient ΔP Co (mass% / 0.1μm)={depth position D Co_MAX Co concentration (mass%) at depth position D Co_15% Co concentration (mass%) at depth D Co_MAX Depth (μm) - Depth position D Co_15% It can be calculated by "depth (μm) at

[0036] In the measurement using a high-frequency glow discharge optical emission analyzer, the hardness of the object to be measured affects the sputtering rate (and sputtering time), and the deeper the point from the outermost layer, the more the measured intensity may be affected by the depth (the depth from the outermost layer to the measurement point). Therefore, for the surface-treated steel sheet 1 of this embodiment, the measurement was started under the measurement conditions set by the method of FIG. 5(A) described above, and the intensity ratio of each element at each measurement point (each depth position) was obtained as the content ratio of each element. Even if the measurement was performed under the same sputtering conditions and HV, the overall numerical value may fluctuate depending on the state of the anode. For example, in the example of FIG. 5(A) described above, the maximum value of the intensity was adjusted to be about 2.0 V, but when the nickel-cobalt-iron diffusion layer 12 of the actually manufactured surface-treated steel sheet 1 was measured, the maximum value of the intensity may not be 2.0 V. However, as described above, the intensity ratio of each element at each measurement point was obtained as the content ratio of each element, so there is no problem.

[0037] In this embodiment, the Co concentration gradient ΔP calculated in this manner Co is 33 mass % / 0.1 μm or less. As a result, when the surface-treated steel sheet 1 is made into a battery container with the nickel-cobalt-iron diffusion layer 12 facing the inner surface, the obtained battery can have a low internal resistance and excellent battery characteristics, and also has excellent corrosion resistance to the electrolyte, making it possible to suppress deterioration of the battery characteristics even after aging.

[0038] That is, it has been known that, in the past, a surface-treated steel sheet 1 used for a battery container is formed with an iron-nickel diffusion layer on the surface, and the iron-nickel diffusion layer is made to be the inner surface of the battery container to expose iron on the inner surface of the battery container, thereby making the battery have superior battery characteristics compared to a case where iron is not exposed. However, if the amount of iron exposed on the inner surface of the battery container is too large, the proportion of nickel present on the inner surface of the battery container decreases accordingly, and when the battery is stored or used for a long period of time, iron dissolves into the electrolyte, and the internal pressure inside the battery increases due to the gas generated by the dissolution of iron, and the increase in internal pressure may cause a defect in which the electrolyte leaks from the sealing part. In addition, the decrease in the proportion of nickel present on the inner surface of the battery container may decrease the rust resistance against the atmosphere when the plate before being molded into a battery container or when stored as a battery container.

[0039] In addition, a method has been known in the past for forming a battery container by forming a nickel-cobalt alloy layer on the surface of a surface-treated steel sheet used for the battery container, and forming the battery container so that the nickel-cobalt alloy layer is the inner surface. In this case, it is known that the battery characteristics can be improved by increasing the content of cobalt in the nickel-cobalt alloy layer. However, when the content of cobalt in the nickel-cobalt alloy layer is increased, the cobalt content is simply increased, and the content of nickel decreases with the increase in the content of cobalt, so that the amount of cobalt that is not alloyed with nickel increases, which also makes the cobalt more likely to dissolve.

[0040] That is, it has been known in the past that the battery characteristics of the resulting battery can be improved by forming an iron-nickel diffusion layer or a nickel-cobalt alloy layer on the inner surface of a battery container and increasing the iron or cobalt content in these layers. However, in this case, the nickel content decreases as the iron or cobalt is added, which causes a problem of reduced rust prevention and corrosion resistance to the electrolyte.

[0041] In contrast, according to the present embodiment, the nickel-cobalt-iron diffusion layer 12 described above is present in the surface-treated steel sheet 1, i.e., the three elements nickel, cobalt and iron coexist, and the Co concentration is at a maximum value at the depth position D Co_MAX The depth position D where the Co concentration is 15% is the maximum value. Co_15% Co concentration gradient ΔP between Co By controlling the content of nickel within the above range, even if the content of nickel, which contributes to improving rust prevention and corrosion resistance to the electrolyte, is relatively low, it is possible to ensure the effect of improving the battery characteristics by exposing iron to an appropriate amount on the inner surface of the battery container, while also achieving excellent corrosion resistance to the electrolyte, and it is possible to suppress deterioration of the battery characteristics even after aging.

[0042] In particular, the present inventors have found that the corrosion resistance to the electrolyte is not determined only by the composition ratio of the surface of the nickel-cobalt-iron or the content of nickel and cobalt. More specifically, the present inventors have found that the distribution of cobalt in the nickel-cobalt-iron diffusion layer varies depending on the manufacturing conditions, and that depending on the manufacturing conditions, cobalt may not spread over the entire thickness direction of the nickel-cobalt-iron diffusion layer, and a region with a high cobalt concentration may be formed partially in the thickness direction, resulting in a steep gradient of the cobalt concentration. In such a case, even if the cobalt concentration on the surface of the nickel-cobalt-iron diffusion layer is low, the corrosion resistance to the electrolyte tends to be poor. In particular, such a distribution is likely to occur when cobalt cannot be sufficiently diffused in the thickness direction, and is also likely to occur when the cobalt concentration on the surface of the plating before heat treatment is high, and is particularly likely to occur when the steel sheet has a cobalt plating layer before heat treatment. This phenomenon is probably caused by the fact that cobalt is more difficult to diffuse than nickel, and therefore, in such cases, it was found that it is necessary to make the gradient of the cobalt concentration gentle by sufficiently diffusing the iron contained in the steel sheet that serves as the base material. In other words, in order to achieve both improved battery characteristics and corrosion resistance to the electrolyte by forming a nickel-cobalt-iron diffusion layer, it is necessary to make the gradient of the cobalt concentration within a specific range by appropriately combining the plating configuration, plating coverage, and heat treatment conditions. In particular, it was found that when selecting a manufacturing method in which a nickel-cobalt-iron diffusion layer is formed by heat treatment after forming a nickel plating layer and a cobalt plating layer, as a manufacturing method that makes it easy to control the total coverage of the nickel and cobalt coverage, it is necessary to take care to make the gradient of the cobalt concentration sufficiently low. From this perspective, it was found that the Co concentration gradient ΔP Co The present invention has been completed by focusing on the above.

[0043] In addition, according to this embodiment, the Co concentration gradient ΔP CoBy making the average particle size distribution in the alumina powder of 33 mass % / 0.1 μm or less, it is possible to obtain a low internal resistance and excellent corrosion resistance against the electrolyte as described above, and in addition, it is possible to suppress the change in color tone over time, thereby suppressing the deterioration of product quality due to discoloration.

[0044] Co concentration gradient ΔP Co The Co concentration gradient ΔP may be 33 mass% / 0.1 μm or less, but is preferably 30 mass% / 0.1 μm or less, more preferably 27 mass% / 0.1 μm or less, and further preferably 24 mass% / 0.1 μm or less. Co The lower limit of is not particularly limited, but is preferably 0.1 mass% / 0.1 μm or more, and more preferably 2 mass% / 0.1 μm or more. Co The unit is "mass% / 0.1 μm", that is, the rate of change in mass% per 0.1 μm.

[0045] In this embodiment, the iron in the nickel-cobalt-iron is preferably the iron diffused from the steel sheet. In the case where the iron diffused from the steel sheet, the Fe concentration increases monotonically from the etching depth at which the Co concentration is at its maximum value toward the steel sheet. In this case, "monotonically increasing" means that the concentration does not decrease midway, and the rate of increase does not have to be constant.

[0046] In this embodiment, the surface-treated steel sheet 1 has a Co concentration gradient ΔP Co In addition to being in the above range, the Ni concentration gradient ΔP Ni In other words, when the Ni concentration, Co concentration, and Fe concentration at each depth position of the nickel-cobalt-iron diffusion layer 12 are obtained by performing the same measurement as above by high-frequency glow discharge optical emission spectrometry on the surface-treated steel sheet 1, the depth position at which the Ni concentration shows the maximum value is defined as D Ni_MAX At the depth position D Ni_MAX The depth position on the steel plate 11 side of the specimen and where the Ni concentration is 15% of the maximum value is defined as DNi_15% In this case, the depth position D Ni_MAX From the depth position D Ni_15% Ni concentration gradient ΔP Ni It is preferable that the content of the nanoparticles is controlled to be 15 mass % / μm or more.

[0047] Here, the Ni concentration gradient ΔP Ni is the Co concentration gradient ΔP Co The specific method is as follows. That is, as shown in FIG. 6B, at point F where the Ni concentration is at its maximum, Ni_MAX The depth position corresponding to Ni_MAX Let F be such a point. Ni_MAX The concentration is at point F Ni_MAX (Depth position D Ni_MAX ) The point F that shows 15% of the maximum Ni concentration shown in Ni_15% The depth position corresponding to Ni_15% In this case, the depth position D Ni_MAX From the depth position D Ni_15% The Ni concentration gradient ΔP Ni As shown in FIG. 6B, the rate of decrease in the Ni concentration is not constant. Ni_MAX and depth position D Ni_15% The rate of change in the Ni concentration measured based on the Ni concentrations at the two points and is called the Ni concentration gradient ΔP Ni In other words, the Ni concentration gradient ΔP Ni (mass% / μm)={depth position D Ni_MAX Ni concentration (mass%) at depth D Ni_15% Ni concentration (mass%) at depth D Ni_MAX Depth (μm) - Depth position D Ni_15% It can be calculated by "depth (μm) at

[0048] Ni concentration gradient ΔP Niis preferably 15 mass% / μm or more, more preferably 17 mass% / μm or more, further preferably 18 mass% / μm or more, and particularly preferably 20 mass% / μm or more. Ni The upper limit of is not particularly limited, but is preferably 90 mass% / μm or less, more preferably 80% or less, and further preferably 50 mass% / μm or less. Ni The unit of is "mass% / μm", that is, the rate of change in mass% per 1 μm. For example, the Ni concentration gradient ΔP Ni is 30 mass% / μm, the depth position D Ni_MAX (Point F Ni_MAX ) is the vertex, and the depth position D Ni_15% (Point F Ni_15% ), it can be seen that as the measurement proceeds in the deeper direction, the Ni concentration decreases at a rate of 30 mass% per 1 μm (3 mass% per 0.1 μm).

[0049] In this embodiment, the Ni concentration, the Co concentration, and the Fe concentration are determined by performing the same measurement as above on the surface-treated steel sheet 1 using high-frequency glow discharge optical emission spectrometry. Among the depth positions at which the Ni concentration in the nickel-cobalt-iron diffusion layer 12 is 0.5% of the maximum value, the depth position located on the surface side is defined as D Ni_0.5% In this case, the depth position D Ni_0.5% Ni concentration P Ni (D Ni_0.5% ), Co concentration P Co (D Ni_0.5% ), Fe concentration P Fe (D Ni_0.5% ) in a specific range, which provides superior battery characteristics when the surface-treated steel sheet 1 is used as a battery container for a battery that uses a strongly alkaline electrolyte, and further reduces the deterioration of the battery characteristics over time.

[0050] As described above, the graph shown in Fig. 5(B) shows the changes in Ni intensity, Co intensity, and Fe intensity in the etching depth direction, and the Ni intensity, Co intensity, and Fe intensity shown in the graph shown in Fig. 5(B) can be directly converted into the mass of Ni, the mass of Co, and the mass of Fe. Therefore, in this embodiment, based on such a graph of Ni intensity, Co intensity, and Fe intensity, a depth position D at which the Ni intensity in the nickel-cobalt-iron diffusion layer 12 is 0.5% of the maximum value is determined. Ni_0.5% Ni concentration P Ni (D Ni_0.5% ), Co concentration P Co (D Ni_0.5% ), and Fe concentration P Fe (D Ni_0.5% ) can be determined by the method described below, and in this embodiment, it is preferable that these be within the ranges described below.

[0051] Below, Ni concentration P Ni (D Ni_0.5% ), Co concentration P Co (D Ni_0.5% ), and Fe concentration P Fe (D Ni_0.5% 5(B), the surface-treated steel sheet 1 of Example 1 according to FIG. 5(B) has a nickel-cobalt-iron diffusion layer 12 in which Ni, Co and Fe coexist in the surface layer portion (region with an etching depth of about 0 to 2.5 μm). As described above, this nickel-cobalt-iron diffusion layer 12 can be formed, for example, by forming a nickel plating layer and a cobalt plating layer in this order on the surface of the steel sheet 11, and then performing a heat treatment under specific conditions, and the iron in the steel sheet 11 is thermally diffused to the outermost surface by the heat treatment. Then, for such nickel-cobalt-iron diffusion layer 12, the maximum value of Ni intensity is extracted, and the depth position at which the intensity is 0.5% of the extracted maximum value is designated as the depth position D. Ni_0.5% In addition, when there are multiple depth positions where the strength is 0.5% of the maximum value, the position closest to the surface of the nickel-cobalt-iron diffusion layer 12 is specified as the depth position DNi_0.5% Specifically, in the graph of FIG. 5(B), the maximum Ni intensity is located near the etching depth position of 0.47 μm, and the intensity is about 1.36 V. Therefore, the intensity of 0.5% of the maximum Ni intensity (1.36 V) is 0.00679 V. From the graph of FIG. 5(C), which is a partially enlarged graph of FIG. 5(B), the depth position D Ni_0.5% In the first embodiment shown in Figs. 5B and 5C, however, the data acquisition intervals for the measurement were set to approximately 0.00465 µm, so the depth position with the closest value to 0.5% intensity was determined to be the specific depth position D Ni_0.5% (In Example 1 shown in FIG. 5(C), the closest etching depth was 0.0558 μm.) However, the inventors of the present invention found that the intensity ratio of each element at a depth position of 0.055 μm was the same as the intensity ratio of each element at a depth position of 0.0558 μm. Ni_0.5% Ni concentration in Ni (D Ni_0.5% ), Co concentration P Co (D Ni_0.5% ), and Fe concentration P Fe (D Ni_0.5% ) can be calculated according to the above-mentioned method. Ni_0.5% Ni concentration P Ni (D Ni_0.5% ), Co concentration P Co (D Ni_0.5% ), and Fe concentration P Fe (D Ni_0.5% ) is focused on at the depth position D Ni_0.5%This is because it can be determined that these concentrations represent the concentration ratios in the surface layer (the outermost layer and the vicinity of the outermost layer) of the nickel-cobalt-iron diffusion layer 12. When the surface-treated steel sheet having the nickel-cobalt-iron diffusion layer of this embodiment is analyzed using a high-frequency glow discharge optical emission spectrometer, the inventors have found that the intensity obtained at the measurement start point is unstable due to the influence of surface roughness and is therefore not stable, whereas a certain degree of strength can be stably obtained regardless of the measurement target by etching to a depth at which the Ni intensity is 0.5% of the maximum value. As described above, in this embodiment, the point at which the Ni intensity is 0.5% of the maximum value is an etching depth of 0.01 to 0.1 μm, which is the outermost layer and the vicinity of the outermost layer of the nickel-cobalt-iron diffusion layer. That is, the Ni concentration P Ni (D Ni_0.5% ), Co concentration P Co (D Ni_0.5% ), and Fe concentration P Fe (D Ni_0.5% ) can be said to substantially represent the Ni concentration, Co concentration, and Fe concentration at the outermost surface of the nickel-cobalt-iron diffusion layer 12.

[0052] In this embodiment, the depth position D Ni_0.5% Co concentration P Co (D Ni_0.5% From the viewpoint of further improving the battery characteristics after aging, the Co concentration P is preferably 5 mass % or more, more preferably 12 mass % or more, further preferably 16 mass % or more, and particularly preferably 20 mass % or more. Co (D Ni_0.5% ) is preferably 65 mass% or less, more preferably 55 mass% or less, even more preferably 39 mass% or less, and particularly preferably 30 mass% or less, from the viewpoint of suppressing the elution of cobalt and thereby suppressing a decrease in corrosion resistance when the surface-treated steel sheet 1 is used as a battery container.

[0053] Also, at depth position D Ni_0.5% Fe concentration P Fe (D Ni_0.5%From the viewpoint of further improving the battery characteristics of the resulting battery, the Fe concentration P is preferably 15% by mass or more, more preferably 20% by mass or more, further preferably 25% by mass or more, and particularly preferably 30% by mass or more. Fe (D Ni_0.5% The lower limit of the content of ) is preferably 90 mass% or less, more preferably 85 mass% or less, even more preferably 75 mass% or less, and particularly preferably 70 mass% or less, from the viewpoint of suppressing the elution of iron and thereby suppressing a decrease in corrosion resistance when the surface-treated steel sheet 1 is used as a battery container.

[0054] Furthermore, in this embodiment, the depth position D Ni_0.5% Ni concentration P Ni (D Ni_0.5% ) is preferably 70 mass % or less, more preferably 60 mass % or less, further preferably 55 mass % or less, and particularly preferably 50 mass % or less, from the viewpoint of suppressing an increase in contact resistance when the surface-treated steel sheet 1 is used as a battery container and from the viewpoint of improving battery characteristics. Ni (D Ni_0.5% The lower limit of the content of ) is preferably 5 mass% or more, more preferably 7 mass% or more, even more preferably 10 mass% or more, and particularly preferably 12 mass% or more, from the viewpoint of more appropriately suppressing the dissolution of cobalt and iron when the surface-treated steel sheet 1 is used as a battery container.

[0055] In addition, in the surface-treated steel sheet 1 of this embodiment, the Co concentration P Co (D Ni_0.5% ) versus Fe concentration P Fe (D Ni_0.5% ) ratio R Fe / Co (P Fe (D Ni_0.5% ) / P Co (D Ni_0.5% The lower limit of the ratio R is preferably 0.5 or more, more preferably 0.8 or more, and even more preferably 1.0 or more, and the upper limit is preferably 20 or less, more preferably 14 or less, and even more preferably 8.0 or less. Fe / CoBy setting the content of the sintered body in the above range, it is possible to achieve a high degree of balance between the effect of improving the battery characteristics of the resulting battery and the effect of improving the corrosion resistance to the electrolyte.

[0056] In addition, from the viewpoint of further improving the initial battery characteristics, the Fe concentration P Fe (D Ni_0.5% ) is preferably 55 mass% or more, more preferably 65 mass% or more. In this case, in order to suppress dissolution into the electrolyte, the Co concentration P Co (D Ni_0.5% ) is preferably 5 mass % or more, and the cobalt content in the nickel-cobalt-iron diffusion layer 12 described later is preferably 0.2 g / m 2 It is preferable that the total content of nickel and cobalt in the nickel-cobalt-iron diffusion layer 12 is 1.6 g / m or more. 2 In this case, from the viewpoint of improving the battery characteristics after aging, the cobalt content in the nickel-cobalt-iron diffusion layer 12 is more preferably 0.5 g / m 2 More preferably, it is 0.7 g / m 2 By setting the cobalt content to the above value, not only the Co content in the surface layer but also a certain amount of cobalt in the diffusion layer can be contained, thereby making it possible to provide excellent battery characteristics after aging.

[0057] In this embodiment, as in the surface-treated steel sheet 1a shown in Fig. 7, an iron-nickel diffusion layer 15 may be further provided between the steel sheet 11 and the nickel-cobalt-iron diffusion layer 12. This makes it possible to further improve the corrosion resistance against the electrolyte when the surface-treated steel sheet 1a is used as a battery container.

[0058] In the surface-treated steel sheet 1a of this embodiment, the presence of the iron-nickel diffusion layer 15 can be confirmed by the following method. That is, when the Ni intensity, Co intensity, and Fe intensity are continuously measured in the depth direction from the surface of the nickel-cobalt-iron diffusion layer 12 toward the steel sheet 11 by high-frequency glow discharge optical emission spectrometry for the surface-treated steel sheet 1a in the same manner as in Fig. 5(B) described above, if there exists a region from a depth at which the Co intensity measured from the surface of the nickel-cobalt-iron diffusion layer 12 toward the depth direction reaches its maximum value and then becomes 15% of the maximum value, to a depth at which the Ni intensity measured from the surface of the nickel-cobalt-iron diffusion layer 12 toward the depth direction reaches its maximum value and then becomes 15% of the maximum value, it can be determined that such a depth region is a diffusion layer made of iron and nickel not containing cobalt, i.e., an iron-nickel diffusion layer, and in this case, it can be determined that an iron-nickel diffusion layer exists. In measurements using a radio frequency glow discharge optical emission spectrometer, as etching progresses, elemental information from the side walls of the etched area becomes more readily available, and elements present in the surface layer are more likely to be detected as noise. Therefore, when the intensity of an element is 15% or less of its maximum intensity at a depth sufficiently deeper than the surface layer or near the surface, it can usually be assumed that that element is hardly present at all.

[0059] In this embodiment, the lower limit of the cobalt content in the nickel-cobalt-iron diffusion layer 12 is preferably 0.2 g / m 2 From the viewpoint of further improving the battery characteristics, it is more preferably 0.5 g / m 2 More preferably, it is 0.7 g / m 2 The upper limit of the cobalt content is preferably 5.0 g / m from the viewpoint of suppressing excessive elution of cobalt from the diffusion layer. 2 More preferably, it is 3.0 g / m or less. 2 More preferably, it is 2.0 g / m or less. 2 The following is the result.

[0060] When the iron-nickel diffusion layer 15 is formed, the lower limit of the total content of nickel contained in the nickel-cobalt-iron diffusion layer 12 and the iron-nickel diffusion layer 15 is preferably 1.0 g / m from the viewpoint of improving corrosion resistance. 2 More preferably, it is 1.3 g / m or more. 2 More preferably, it is 1.6 g / m or more. 2 The upper limit of the total content of nickel contained in the nickel-cobalt-iron diffusion layer 12 and the iron-nickel diffusion layer 15 is preferably 12.5 g / m because if the layer is too thick, it may be difficult to expose iron or a stable ratio may not be achieved. 2 More preferably, it is 9.5 g / m or less. 2 or less, more preferably 8.5 g / m 2 or less, and particularly preferably 7.0 g / m 2 The following is the result.

[0061] In addition, when the iron-nickel diffusion layer 15 is not formed, the lower limit of the nickel content in the nickel-cobalt-iron diffusion layer 12 is preferably 0.2 g / m from the viewpoint of improving corrosion resistance. 2 More preferably, 0.5 g / m 2 More preferably, 0.7 g / m 2 In the case where the iron-nickel diffusion layer 15 is not formed, the upper limit of the nickel content in the nickel-cobalt-iron diffusion layer 12 is preferably 11.3 g / m because if the layer is too thick, it may be difficult to expose the iron or a stable ratio may not be achieved. 2 Less than or equal to 9.5 g / m 2 Less than 8.5 g / m, more preferably 8.5 g / m 2 Less than 7.0 g / m 2 The following is the result.

[0062] The total content of nickel and cobalt in the nickel-cobalt-iron diffusion layer 12 (when the iron-nickel diffusion layer 15 is formed, the total amount of nickel and cobalt contained in the nickel-cobalt-iron diffusion layer 12 and the iron-nickel diffusion layer 15) is preferably 1.6 g / m from the viewpoint of suppressing elution from the base steel. 2 More preferably, it is 2.5 g / m or more. 2 More preferably, it is 3.0 g / m 2 More preferably, 3.5 g / m 2 The upper limit of the total content of nickel and cobalt is preferably 14.0 g / m2, since if the thickness is too thick, it may be difficult to expose iron or a stable ratio may not be achieved. 2 More preferably, it is 10.0 g / m or less. 2 More preferably, it is 9.0 g / m or less. 2 or less, and particularly preferably 7.5 g / m 2 The following is the result.

[0063] The nickel content and cobalt content described above can be determined, for example, by subjecting the surface-treated steel sheets 1, 1a to fluorescent X-ray analysis and measuring the respective deposition amounts of nickel and cobalt based on a previously obtained calibration curve.

[0064] In addition, when measuring the amount of adhesion, a semi-quantitative analysis (calculation of the composition ratio of any element) can also be performed by fluorescent X-ray analysis. However, since the penetration depth of X-rays is 10 μm or more, the nickel and cobalt content of the nickel-cobalt-iron diffusion layer 12 is 14.0 g / m 2 If the Ni concentration is less than 100%, the ratio will include the iron in the substrate even if the measurement is performed from the outermost layer. For example, in the case of the surface-treated steel sheet of Example 1 described later (the value obtained by high-frequency glow discharge optical emission spectrometry is the Ni concentration P Ni (D Ni_0.5% )=23.50% by mass, Co concentration P Co (D Ni_0.5% )=15.14% by mass, Fe concentration P Fe (D Ni_0.5%When X-ray fluorescence analysis is performed on a surface-treated steel sheet (copper alloy steel sheet having a nickel content of 1.0 mass % or less and a nickel content of 1.0 mass % or less) (cobalt content of 1.0 mass % or less, nickel content of 1.0 mass % or less and iron content of 13.6 mass %, cobalt content of 5.6 mass %, and iron content of 80.8 mass %, respectively, the measurement results by X-ray fluorescence analysis are different from the measurement results by radio frequency glow discharge optical emission spectrometry. Therefore, particularly when iron is exposed to the surface layer, the ratios calculated from the plating coating weight and X-ray fluorescence analysis are different from the ratios of the surface layer (the outermost layer and the vicinity of the outermost layer) analyzed by radio frequency glow discharge optical emission spectrometry. In contrast, radio frequency glow discharge optical emission spectrometry makes it possible to appropriately analyze the ratios of the surface layer (the outermost layer and the vicinity of the outermost layer).

[0065] The surface-treated steel sheets 1, 1a of the present embodiment are configured as described above.

[0066] The surface-treated steel sheet 1, 1a of this embodiment is formed into a positive electrode can 21 of an alkaline battery 2 shown in Figures 1 and 2 or a battery container for other batteries by a deep drawing method, a draw-and-ironing method (DI method), a draw-and-stretch method (DTR method), or a method that combines drawing, stretching, and ironing, etc., so that the nickel-cobalt-iron diffusion layer 12 is on the inner surface side of the container.

[0067] The battery container of the present embodiment is made of the surface-treated steel sheet 1, 1a of the present embodiment described above, and therefore when used as a battery, it can have a low internal resistance and excellent battery characteristics, and can also have excellent corrosion resistance against a strong alkaline electrolyte, making it possible to suppress the deterioration of battery characteristics even after aging, and can be suitably used as a battery container for a battery using a strong alkaline electrolyte. In the above example, the surface-treated steel sheet 1, 1a of the present embodiment is used as a member of an alkaline battery, but is not limited to alkaline batteries, and the surface-treated steel sheet 1, 1a of the present embodiment can be suitably used as a battery container for a battery using a strong alkaline electrolyte. In particular, the battery container of the present embodiment can be suitably used as a battery container for a battery equipped with a mechanism for releasing gas generated inside the battery. When such a gas release mechanism is provided, even if a very small amount of cobalt or iron is dissolved from the nickel-cobalt-iron diffusion layer 12 formed on the inner surface side of the battery container of the present embodiment, which generates a small amount of gas, the generated gas can be appropriately released.

[0068] <Method of manufacturing surface-treated steel sheet> Next, a method for producing the surface-treated steel sheet 1 of this embodiment will be described.

[0069] First, a steel sheet 11 is prepared, and nickel plating is applied to the steel sheet 11 to form a nickel plating layer 13 on the surface of the steel sheet 11 that will become the inner surface of the battery container, as shown in Fig. 4. The nickel plating layer 13 is preferably formed not only on the surface of the steel sheet 11 that will become the inner surface of the battery container, but also on the opposite surface. When forming the nickel plating layer 13 on both sides of the steel sheet 11, nickel plating layers 13 having different compositions and surface roughness may be formed on the surface of the steel sheet 11 that will become the inner surface of the battery container and the surface of the steel sheet 11 that will become the outer surface of the battery container using plating baths of different compositions, but from the viewpoint of improving production efficiency, the nickel plating layer 13 may be formed on both sides of the steel sheet 11 in one step using the same plating bath.

[0070] The nickel plating bath for forming the nickel plating layer 13 is not particularly limited, and plating baths commonly used in electrolytic nickel plating, such as a Watts bath, a sulfamic acid bath, a boron fluoride bath, a chloride bath, a citric acid bath, etc., can be used. For example, the nickel plating layer 13 can be formed using a Watts bath with a bath composition of 200 to 350 g / L of nickel sulfate, 20 to 60 g / L of nickel chloride, and 10 to 50 g / L of boric acid, at a pH of 3.0 to 4.8 (preferably pH 3.6 to 4.6), a bath temperature of 50 to 70° C., and a current density of 0.5 to 60 A / dm 2 (Preferably 1 to 40 A / dm 2 ) can be formed.

[0071] The nickel content in the nickel plating layer 13 is 12.5 g / m 2 It is sufficient if it is less than 10.0 g / m 2 Less than 9.0 g / m 2 Less than 8.8 g / m, more preferably 8.8 g / m 2 The nickel content can be determined by measuring the amount of nickel atoms that constitute the nickel plating layer 13 by performing fluorescent X-ray analysis on the steel sheet 11 on which the nickel plating layer 13 is formed. The lower limit of the nickel content in the nickel plating layer 13 is not particularly limited, but is preferably 0.2 g / m 2 More preferably, 0.4 g / m 2 More preferably, 0.8 g / m 2 More preferably, 1.2 g / m 2 From the viewpoint of further improving corrosion resistance, it is particularly preferable to use a coating weight of 1.6 g / m 2That is all. By setting the nickel content in the nickel plating layer 13 within the above range, as described below, when the cobalt plating layer 14 is formed on the nickel plating layer 13 and then heat-treated to form the nickel-cobalt-iron diffusion layer 12, the iron constituting the steel sheet 11 can be thermally diffused more satisfactorily by the heat treatment through the nickel plating layer 13 to the surface of the cobalt plating layer 14, thereby making it possible to more satisfactorily form the nickel-cobalt-iron diffusion layer 12.

[0072] Next, the steel sheet 11 on which the nickel plating layer 13 has been formed is subjected to cobalt plating to form the cobalt plating layer 14.

[0073] The cobalt plating bath for forming the cobalt plating layer 14 is not particularly limited, but a cobalt plating bath having a bath composition of cobalt sulfate: 200 to 300 g / L, cobalt chloride: 50 to 150 g / L, sodium chloride: 10 to 50 g / L, and boric acid: 10 to 60 g / L is used, and the pH is 2 to 5, the bath temperature is 40 to 80° C., and the current density is 1 to 40 A / dm 2 It can be formed under the conditions of

[0074] The lower limit of the cobalt content in the cobalt plating layer 14 is not particularly limited, but is preferably 0.2 g / m 2 More preferably, 0.4 g / m 2 More preferably, 0.6 g / m 2 More preferably, 0.8 g / m 2 From the viewpoint of further improving corrosion resistance, it is particularly preferable to use a coating weight of 1.0 g / m 2 The upper limit is not particularly limited, but from the viewpoint of suppressing excessive elution of cobalt from the diffusion layer, it is preferably 5.0 g / m 2 More preferably, it is 3.0 g / m or less. 2 More preferably, it is 2.0 g / m or less. 2By setting the content of cobalt in the cobalt plating layer 14 within the above range, when the steel sheet 11 having the nickel plating layer 13 and the cobalt plating layer 14 formed thereon is subjected to a heat treatment as described below, the iron constituting the steel sheet 11 can be thermally diffused more satisfactorily by the heat treatment through the nickel plating layer 13 to the surface of the cobalt plating layer 14, thereby making it possible to more satisfactorily form the nickel-cobalt-iron diffusion layer 12.

[0075] Next, the steel sheet 11 on which the nickel plating layer 13 and the cobalt plating layer 14 are formed is subjected to a heat treatment, whereby the iron constituting the steel sheet 11, the nickel constituting the nickel plating layer 13, and the nickel and cobalt constituting the cobalt plating layer 14 are thermally diffused to each other, thereby forming a nickel-cobalt-iron diffusion layer 12. As a result, a surface-treated steel sheet 1 in which the nickel-cobalt-iron diffusion layer 12 is formed on the steel sheet 11 is obtained as shown in Fig. 3. Alternatively, depending on the content of nickel in the nickel plating layer 13, the total content of nickel and cobalt in the cobalt plating layer 14, the conditions of the heat treatment, etc., a surface-treated steel sheet 1a in which an iron-nickel diffusion layer 15 is formed between the steel sheet 11 and the nickel-cobalt-iron diffusion layer 12 is obtained as shown in Fig. 7.

[0076] The heat treatment conditions may be appropriately selected depending on the nickel content in the nickel plating layer 13 and the total content of nickel and cobalt in the cobalt plating layer 14. In other words, the heat treatment conditions may be selected by a combination of temperature and time that provide a heat quantity sufficient for the iron in the steel sheet to be sufficiently diffused. For example, in continuous annealing, the heat treatment temperature may be 480 to 900°C, and the total content of nickel and cobalt may be 2.7 g / m 2In the above cases, the temperature is preferably 650 to 850°C, and more preferably 680 to 840°C. The soaking time in the heat treatment (the time for maintaining the heat treatment temperature) is preferably 10 seconds to 2 minutes, more preferably 10 seconds to 1.5 minutes, and even more preferably 20 to 70 seconds. The heat treatment conditions that can provide a heat quantity sufficient for the iron in the steel sheet to be sufficiently diffused are, for example, 4.5 g / m 2 In the above cases, holding at 700°C or more and less than 750°C for 1 minute or more or at 750°C to 840°C for 20 seconds to 1.5 minutes is preferred. In box annealing, the heat treatment temperature is preferably 450 to 680°C, more preferably 500°C to 650°C. In box annealing, the soaking time may be appropriately selected within the range of 1 to 24 hours depending on the total content of nickel and cobalt and the heat treatment temperature, and is preferably 3 to 20 hours, more preferably 6 to 18 hours. As the method of thermal diffusion treatment, either continuous annealing or box annealing may be used, but continuous annealing is preferred from the viewpoint of good productivity in continuous steel strip, and box annealing is preferred from the viewpoint of exposing more iron and improving battery characteristics. In particular, in the production of continuous steel strips, box annealing is generally performed on the steel strip in a rolled state. If the heat treatment temperature in the box annealing is too high, cobalt will diffuse from the nickel-cobalt-iron diffusion layer 12 formed on the surface to the back surface in contact with it, resulting in unstable quality. In addition, the Ni concentration gradient ΔP Ni tends to be too low.

[0077] In the above manner, the surface-treated steel sheet 1, 1a of the present embodiment can be manufactured. In particular, in the present embodiment, the steel sheet 11 on which the nickel plating layer 13 and the cobalt plating layer 14 are formed in this order is subjected to heat treatment, so that the iron constituting the steel sheet 11, the nickel constituting the nickel plating layer 13, and the cobalt plating layer 14 are thermally diffused to each other to form the nickel-cobalt-iron diffusion layer 12. In comparison with the case where a nickel-cobalt alloy plating layer is formed instead of the cobalt plating layer 14, for example, the nickel amount and cobalt amount in the obtained nickel-cobalt-iron diffusion layer 12 can be easily controlled to a desired range when manufacturing the continuous steel strip, thereby realizing excellent productivity.

[0078] According to the manufacturing method of this embodiment, the content of nickel contained in the nickel plating layer 13, the total content of nickel and cobalt contained in the cobalt plating layer 14, and the heat treatment conditions are controlled to be within the above-mentioned ranges, so that the Co concentration gradient ΔP CoHowever, the thickness of the surface-treated steel sheet 1, 1a of the present embodiment can be controlled to 33 mass % / 0.1 μm or less. As a result, according to the manufacturing method of the present embodiment, when the surface-treated steel sheet 1, 1a of the present embodiment is used as a battery container, the battery obtained can have a low internal resistance and excellent battery characteristics, and can also have excellent corrosion resistance against a strong alkaline electrolyte, and can suppress the deterioration of the battery characteristics even after aging. Therefore, the battery can be preferably used as a battery container for a battery using a strong alkaline electrolyte. In particular, even if a small amount of gas is generated due to the elution of cobalt or iron in the nickel-cobalt-iron diffusion layer 12 formed on the inner surface side of the container, the generated gas can be appropriately released, so that the battery can be preferably used as a battery container for a battery equipped with a mechanism for releasing the gas generated inside the battery. In particular, in the manufacturing method in which the nickel plating is followed by cobalt plating and heat treatment is performed, Co on the substrate side is easily diffused and Co is easily left in the region close to the surface, so that the Co distribution is likely to form a region where Co is concentrated in the region close to the surface, and therefore, the half-width W of the Co concentration in the nickel-cobalt-iron diffusion layer 12 is preferably 100%. Co However, by setting the Co concentration gradient in a specific range, it is possible to further increase the effect of reducing the internal resistance and the effect of improving the corrosion resistance against a strong alkaline electrolyte. Co As shown in Fig. 6(C), which is a graph obtained by changing the scale of the horizontal axis of the graph in Fig. 6(A), the point F Co_MAX The depth position D shows 50% Co concentration compared to the Co concentration in Co_50%_ini and depth position D Co_50%_end (i.e., |Depth position D Co_50%_ini Depth (μm) - Depth position D Co_50%_end This can be obtained by calculating the depth (μm) at

[0079] In the above, a method has been exemplified in which the nickel plating layer 13 and the cobalt plating layer 14 are formed in this order on the surface of the steel sheet 11, and then a heat treatment is performed to thermally diffuse the iron, nickel, and cobalt contained in each layer, thereby forming the nickel-cobalt-iron diffusion layer 12. However, instead of this method, a method may be adopted in which, without forming the nickel plating layer 13, only the nickel-cobalt alloy plating layer 14' is directly formed on the surface of the steel sheet 11, and then a heat treatment is performed to thermally diffuse the steel sheet 11 and the nickel-cobalt alloy plating layer 14', thereby forming the nickel-cobalt-iron diffusion layer 12. Hereinafter, a manufacturing method of the surface-treated steel sheet 1 will be described in which, without forming the nickel plating layer 13, only the nickel-cobalt alloy plating layer 14' is formed, and then heat treatment is performed to form the nickel-cobalt-iron diffusion layer 12.

[0080] The nickel-cobalt alloy plating bath for forming the nickel-cobalt alloy plating layer 14' is not particularly limited, but it is preferable to use a plating bath based on a Watts bath containing nickel sulfate, nickel chloride, cobalt sulfate and boric acid. The cobalt / nickel ratio in the nickel-cobalt alloy plating bath is preferably in the range of 0.05 to 1.0, more preferably in the range of 0.1 to 0.7, in terms of the molar ratio of cobalt / nickel. For example, when using a plating bath based on a Watts bath containing nickel sulfate, nickel chloride, cobalt sulfate and boric acid, the components of the plating bath can be appropriately adjusted so that the cobalt / nickel ratio falls within the above ranges: nickel sulfate: 10 to 300 g / L, nickel chloride: 20 to 60 g / L, cobalt sulfate: 10 to 250 g / L, and boric acid: 10 to 40 g / L. For nickel-cobalt alloy plating, the bath temperature is 40 to 80°C, pH is 1.5 to 5.0, and the current density is 1 to 40 A / dm 2 It is preferable to set the condition as follows.

[0081] The total content of nickel and cobalt contained in the nickel-cobalt alloy plating layer 14' is preferably 11.5 g / m 2More preferably, it is 10.0 g / m or less. 2 Less than 9.0 g / m 2 Less than 7.5 g / m 2 The nickel and cobalt contents in the nickel-cobalt alloy plating layer 14' can be determined by measuring the total adhesion amount of nickel atoms and cobalt atoms constituting the nickel-cobalt alloy plating layer 14' by performing fluorescent X-ray analysis on the steel sheet 11 on which the nickel-cobalt alloy plating layer 14' is formed. The lower limit of the total content of nickel and cobalt in the nickel-cobalt alloy plating layer 14' is not particularly limited, but is preferably 1.6 g / m 2 More preferably, 2.5 g / m 2 More preferably, 3.0 g / m 2 More preferably, 3.5 g / m 2 By setting the total content of nickel and cobalt contained in the nickel-cobalt alloy plating layer 14' within the above range, when the steel sheet 11 on which the nickel-cobalt alloy plating layer 14' is formed is subjected to a heat treatment as described below, the iron constituting the steel sheet 11 can be thermally diffused more satisfactorily to the surface of the nickel-cobalt alloy plating layer 14' by the heat treatment, and thus the nickel-cobalt-iron diffusion layer 12 can be more satisfactorily formed.

[0082] Next, the steel sheet 11 on which the nickel-cobalt alloy plating layer 14' has been formed is subjected to a heat treatment, whereby the iron constituting the steel sheet 11 and the nickel and cobalt constituting the nickel-cobalt alloy plating layer 14' are thermally diffused into each other to form a nickel-cobalt-iron diffusion layer 12. As a result, as shown in Fig. 3, a surface-treated steel sheet 1 having the nickel-cobalt-iron diffusion layer 12 formed on the steel sheet 11 is obtained. Note that, due to the nature of the manufacturing method, this manufacturing method is not suitable for a configuration in which an iron-nickel diffusion layer 15 is further provided between the steel sheet 11 and the nickel-cobalt-iron diffusion layer 12, as in the case of a surface-treated steel sheet 1a shown in Fig. 6.

[0083] The heat treatment conditions may be appropriately selected depending on the total content of nickel and cobalt contained in the nickel-cobalt alloy plating layer 14', but the heat treatment temperature is preferably 480 to 900°C, more preferably 500 to 800°C, and even more preferably 520 to 750°C. The soaking time in the heat treatment (the time for maintaining the above heat treatment temperature) is preferably 3 seconds to 2 minutes, more preferably 10 seconds to 1.5 minutes, and even more preferably 20 to 60 seconds. As the method of thermal diffusion treatment, either continuous annealing or box annealing may be used, but continuous annealing is preferred from the viewpoint of ease of adjusting the heat treatment temperature and heat treatment time to the above ranges.

[0084] According to the above manufacturing method, the total content of nickel and cobalt contained in the nickel-cobalt alloy plating layer 14 and the heat treatment conditions are controlled to the above ranges, so that the nickel-cobalt-iron diffusion layer 12 formed has a Co concentration gradient controlled to 33% / 0.1 μm or less. As a result, when the surface-treated steel sheet 1 of the present embodiment is used as a battery container, the resulting battery can have a low internal resistance and excellent battery characteristics, and can also have excellent corrosion resistance against a strong alkaline electrolyte, making it possible to suppress the deterioration of battery characteristics even after aging, and can be suitably used as a battery container for a battery using a strong alkaline electrolyte. In particular, even if a small amount of gas is generated due to the elution of cobalt or iron in the nickel-cobalt-iron diffusion layer 12 formed on the inner surface side of the container, the generated gas can be appropriately released, so that the battery can be suitably used as a battery container for a battery equipped with a mechanism for releasing gas generated inside the battery.

[0085] Alternatively, a method may be adopted in which, after forming the nickel plating layer 13 in the same manner as described above, the steel sheet 11 on which the nickel plating layer 13 has been formed is subjected to nickel-cobalt alloy plating to form the nickel-cobalt alloy plating layer 14″, and then the nickel-cobalt alloy plating layer 14″ is subjected to a heat treatment.

[0086] The nickel-cobalt alloy plating bath for forming the nickel-cobalt alloy plating layer 14'' is not particularly limited, but it is preferable to use a plating bath based on a Watts bath containing nickel sulfate, nickel chloride, cobalt sulfate and boric acid. The cobalt / nickel ratio in the nickel-cobalt alloy plating bath is preferably in the range of 0.05 to 1.0, more preferably in the range of 0.1 to 0.7, in terms of the molar ratio of cobalt / nickel. For example, when using a plating bath based on a Watts bath containing nickel sulfate, nickel chloride, cobalt sulfate and boric acid, a plating bath can be used in which the components are appropriately adjusted so that the cobalt / nickel ratio falls within the above ranges of nickel sulfate: 10 to 300 g / L, nickel chloride: 20 to 60 g / L, cobalt sulfate: 10 to 250 g / L, and boric acid: 10 to 40 g / L. For nickel-cobalt alloy plating, the bath temperature is 40 to 80°C, pH is 1.5 to 5.0, and the current density is 1 to 40 A / dm 2 It is preferable to set the condition as follows.

[0087] The total content of nickel and cobalt in the nickel-cobalt alloy plating layer 14 ″ is 7.5 g / m 2 It is sufficient if it is less than 4.0 g / m 2 Less than or equal to 3.0 g / m 2 The nickel and cobalt contents in the nickel-cobalt alloy plating layer 14'' can be determined by measuring the total adhesion amount of nickel atoms and cobalt atoms constituting the nickel plating layer 13 and the nickel-cobalt alloy plating layer 14'' by performing fluorescent X-ray analysis on the steel sheet 11 on which the nickel plating layer 13 and the nickel-cobalt alloy plating layer 14'' are formed, and subtracting the nickel content in the nickel plating layer 13 described above from the obtained total adhesion amount (or by subtracting the adhesion amount of nickel when forming the nickel plating layer 13). The lower limit of the total content of nickel and cobalt in the nickel-cobalt alloy plating layer 14'' is not particularly limited, but is preferably 0.4 g / m 2 More preferably, 0.8 g / m2 More preferably, 1.2 g / m 2 More preferably, 1.6 g / m 2 That is all. By setting the total content of nickel and cobalt contained in the nickel-cobalt alloy plating layer 14'' within the above range, when the steel sheet 11 on which the nickel plating layer 13 and the nickel-cobalt alloy plating layer 14'' are formed is subjected to a heat treatment as described below, iron constituting the steel sheet 11 can be thermally diffused more satisfactorily by the heat treatment through the nickel plating layer 13 to the surface of the nickel-cobalt alloy plating layer 14'', thereby making it possible to more satisfactorily form the nickel-cobalt-iron diffusion layer 12.

[0088] The content of cobalt in the nickel-cobalt alloy plating layer 14 ″ is 0.2 g / m 2 It is preferable that the density is equal to or higher than 0.5 g / m in order to further improve the battery characteristics of the obtained battery. 2 More preferably, 0.7 g / m 2 The upper limit of the cobalt content is not particularly limited as long as it does not hinder the content ratio of the surface layer from being within a predetermined range, but if the cobalt content is too high, it may be difficult to expose iron, so that the upper limit is preferably 5.0 g / m 2 Less than or equal to 3.0 g / m 2 Less than 2.0 g / m, more preferably 2.0 g / m 2 The cobalt content can be determined by measuring the amount of cobalt atoms adhering to the nickel-cobalt alloy plating layer 14'' by performing fluorescent X-ray analysis on the steel sheet 11 on which the nickel plating layer 13 and the nickel-cobalt alloy plating layer 14'' are formed. By setting the cobalt content in the nickel-cobalt alloy plating layer 14'' to the above range, when the surface-treated steel sheet 1 is used as a battery container, the battery characteristics of the resulting battery can be further improved.

[0089] Next, the steel sheet 11 on which the nickel plating layer 13 and the nickel-cobalt alloy plating layer 14'' are formed is subjected to a heat treatment, whereby the iron constituting the steel sheet 11, the nickel constituting the nickel plating layer 13, and the nickel and cobalt constituting the nickel-cobalt alloy plating layer 14'' are thermally diffused relative to one another to form a nickel-cobalt-iron diffusion layer 12. As a result, as shown in FIG. 3, a surface-treated steel sheet 1 in which the nickel-cobalt-iron diffusion layer 12 is formed on the steel sheet 11 is obtained. Alternatively, depending on the content of nickel in the nickel plating layer 13, the total content of nickel and cobalt in the nickel-cobalt alloy plating layer 14'', the heat treatment conditions, and the like, as shown in FIG. 7, a surface-treated steel sheet 1a in which an iron-nickel diffusion layer 15 is formed between the steel sheet 11 and the nickel-cobalt-iron diffusion layer 12 is obtained.

[0090] The conditions for the heat treatment may be appropriately selected depending on the content of nickel contained in the nickel plating layer 13 and the total content of nickel and cobalt contained in the nickel-cobalt alloy plating layer 14'', but the heat treatment temperature may be 480 to 900°C, preferably 500 to 800°C, and more preferably 520 to 750°C. The soaking time in the heat treatment (the time for maintaining the above heat treatment temperature) is preferably 3 seconds to 2 minutes, more preferably 10 seconds to 1.5 minutes, and even more preferably 20 to 60 seconds. As the method for the thermal diffusion treatment, either continuous annealing or box annealing may be used, but continuous annealing is preferred from the viewpoint of easily adjusting the heat treatment temperature and heat treatment time to the above ranges. Note that when the nickel and cobalt contents are 11.5 g / m 2 When the content of nickel and cobalt is less than 5.4 g / m, continuous annealing at a heat treatment temperature of 600 to 900°C is more preferable, and continuous annealing at a heat treatment temperature of 700 to 830°C is even more preferable, from the viewpoint of more stable exposure of iron. 2 In the following cases, continuous annealing at a heat treatment temperature of 480°C or higher and lower than 600°C may be used. EXAMPLES

[0091] Examples will be given below to describe the present invention more specifically, but the present invention is not limited to these examples. The definitions and evaluation methods of each property are as follows.

[0092] <Nickel content and cobalt content> The surface of the surface-treated steel sheet was measured with a fluorescent X-ray analyzer (ZSX100e, manufactured by Rigaku Corporation) to measure the nickel content and cobalt content contained in the nickel-cobalt-iron diffusion layer (when an iron-nickel diffusion layer is formed between the steel sheet and the nickel-cobalt-iron diffusion layer, the total nickel content and cobalt content contained in the nickel-cobalt-iron diffusion layer and the iron-nickel diffusion layer), respectively.

[0093] <Co concentration gradient ΔP Co , Ni concentration gradient ΔP Ni , Ni concentration P Ni (D Ni_0.5% ), Co concentration P Co (D Ni_0.5% ), Fe concentration P Fe (D Ni_0.5% )> For the surface-treated steel sheet, according to the method described above, the Ni intensity, Co intensity, and Fe intensity were continuously measured in the depth direction from the surface side of the nickel-cobalt-iron diffusion layer toward the steel sheet by high-frequency glow discharge optical emission spectrometry. Based on the obtained Ni intensity, Co intensity, and Fe intensity, the Ni concentration, Co concentration, and Fe concentration were respectively determined. Based on the determined results, the Co concentration gradient ΔP Co , Ni concentration gradient ΔP Ni , Ni concentration P Ni (D Ni_0.5% ), Co concentration P Co (D Ni_0.5% ), and Fe concentration P Fe (D Ni_0.5% ) were determined. Also, based on the determined Co concentration P Co (D Ni_0.5% ), and Fe concentration P Fe (D Ni_0.5% ), the Fe concentration P Co (D Ni_0.5% ) with respect to the Co concentration P Fe (DNi_0.5% ) ratio R Fe / Co (P Fe (D Ni_0.5% ) / P Co (D Ni_0.5% The measurement conditions by high-frequency glow discharge optical emission spectrometry were as follows: Measurement equipment: Marcus type high-frequency glow discharge optical emission surface analyzer (Horiba, model number: GD-Profiler2) Photomultiplier channel voltage (HV): Fe 785V, Ni 630V, Co 720V Anode diameter: φ4mm Gas type: Ar Capture interval: 0.05 seconds Gas pressure: 600Pa Output: 35W

[0094] <Corrosion current density> The surface-treated steel sheet was cut to prepare a rectangular test piece with a width of 20 mm and a length of 40 mm. The test piece thus prepared was then immersed in a 10M potassium hydroxide aqueous solution with a measurement area of ​​φ6 mm and a liquid temperature of 25°C, and measurement was performed using an electrochemical measurement system (manufactured by Hokuto Denko Corporation, model number: HZ-5000) with a silver / silver chloride electrode as the reference electrode and platinum as the counter electrode, sweeping from -800 mV to 800 mV at a rate of 50 mV / min. Based on the measurement results, the current density at the potential of 100 mV was obtained as the corrosion current density. In addition, in the evaluation of the corrosion current density, the corrosion current density was measured when the corrosion current density was 0.025 mA / cm 2 Less than or equal to 0.015 mA / cm 2 If the measured value was equal to or less than this value, the surface-treated steel sheet was judged to have excellent resistance to elution.

[0095] <Contact resistance value> The surface-treated steel plate was cut to prepare a No. 13B test piece according to JIS Z 2241:2011 "Metallic Material Tensile Test Method". Next, one of the prepared test pieces was measured using an electric contact simulator (manufactured by Yamazaki Precision Laboratory Co., Ltd., model number: CRS-1) under the condition of a contact load of 100 gf, to obtain the first contact resistance value of the test piece. Next, the test piece for which the first contact resistance value was measured was subjected to a tensile test using a bench-top precision universal testing machine (manufactured by Shimadzu Corporation, model number: AGS-X) under the condition of a tensile rate of 20%, and the test piece obtained after the tensile test was similarly measured to obtain the second contact resistance value of the test piece. Furthermore, the test piece for which the second contact resistance value was measured was immersed in a potassium hydroxide aqueous solution with a concentration of 10 M at 60°C for 20 days, and then pulled out of the potassium hydroxide aqueous solution and similarly measured to obtain the third contact resistance value of the test piece. The measured contact resistance values ​​are shown in Table 1, which will be described later. In Table 1, the first contact resistance value is shown as "before tension", the second contact resistance value is shown as "before aging", and the third contact resistance value is shown as "after aging". In Table 1, the difference between the second and third contact resistance values ​​is shown as "change before and after aging". In the evaluation of the contact resistance value, if the measured value "after aging" is 12 mΩ or less, it is determined that the surface-treated steel sheet is capable of suppressing the deterioration of battery characteristics after aging, and if it is 10 mΩ or less, and especially if it is 8 mΩ or less, it is determined that the deterioration of the battery characteristics is even more capable of suppressing.

[0096] <Color change due to constant temperature and humidity testing> A constant temperature and humidity test was performed on the surface-treated steel sheet using a constant temperature and humidity chamber (product name "LHL-113", manufactured by Espec Corporation) under conditions of a temperature of 55°C and a humidity of 85% for 400 hours. Then, before and after the constant temperature and humidity test, the surface of the surface-treated steel sheet on which the nickel-cobalt-iron diffusion layer was formed was measured using a spectrophotometer (product name "CM-5", manufactured by Konica Minolta Japan, Inc.) to measure the amount of change in color tone (ΔL *The measurement conditions for the spectrophotometer were as follows: main light source: D65, field of view: 10°, measurement method: reflection, specular reflection light treatment: SCE, measurement diameter: φ8 mm. The amount of color change (ΔL * It can be judged that the smaller the value of ) is, the smaller the color change over time is, and the more the deterioration of the product due to discoloration is suppressed. The evaluation of the color change by the constant temperature and humidity test was performed for Examples 3 and 4 and Comparative Examples 4, 6, and 12.

[0097] Example 1 As the metal sheet, a steel sheet was prepared by annealing a TM rolled sheet (thickness: 0.25 mm) of low carbon aluminum-killed steel having the chemical composition shown below. C: 0.04% by weight, Mn: 0.21% by weight, Si: 0.02% by weight, P: 0.012% by weight, S: 0.009% by weight, Al: 0.061% by weight, N: 0.0036% by weight, balance: Fe and inevitable impurities.

[0098] The prepared steel sheet was then subjected to alkaline electrolytic degreasing, pickling by immersion in sulfuric acid, and nickel plating under the following conditions, resulting in a nickel coating weight of 3.81 g / m 2 A nickel plating layer having the following composition was formed. <Nickel plating> Bath composition: Nickel sulfate 250g / L, nickel chloride 45g / L, boric acid 30g / L pH: 3.6~4.6 Bath temperature: 60℃ Current density: 20A / dm 2

[0099] Next, the steel sheet on which the nickel plating layer was formed was subjected to cobalt plating under the following conditions to form a cobalt plating layer on the nickel plating layer. Note that the conditions for forming the cobalt plating layer were such that the total amount of nickel and cobalt (including the amount of nickel in the underlying nickel plating layer) was the amount shown in Tables 1 and 2. <Cobalt plating> Plating bath composition: Cobalt sulfate 250g / L, cobalt chloride 90g / L, sodium chloride 20g / L, boric acid 30g / L pH: 3.5~5.0 Bath temperature: 60℃ Current density: 10A / dm 2

[0100] Next, the steel sheet on which the nickel plating layer and the cobalt plating layer were formed was subjected to continuous annealing (heat treatment) at a heat treatment temperature of 800°C for 40 seconds to form a nickel-cobalt-iron diffusion layer, thereby obtaining a surface-treated steel sheet. The Ni amount, Co amount, and Co concentration gradient ΔP of the obtained surface-treated steel sheet were measured according to the above method. Co , Ni concentration P Ni (D Ni_0.5% ), Co concentration P Co (D Ni_0.5% ), Fe concentration P Fe (D Ni_0.5% ), corrosion current density, and contact resistance were evaluated. The results are shown in Tables 1 and 2 and Figures 5(B), 6(A), and 6(B). Figures 5(B), 6(A), and 6(B) show the Co concentration gradient ΔP Co , Ni concentration gradient ΔP Ni , Ni concentration P Ni (D Ni_0.5% ), Co concentration P Co (D Ni_0.5% ), and Fe concentration P Fe (D Ni_0.5% 2 is a graph showing the results of measuring the surface-treated steel sheet by high-frequency glow discharge optical emission spectrometry when determining the thermal conductivity (Tc) of the steel sheet.

[0101] Examples 2 to 5 Surface-treated steel sheets were produced and evaluated in the same manner as in Example 1, except that the amount of nickel deposited when forming the nickel plating layer, the conditions when forming the cobalt plating layer, and the heat treatment temperature and heat treatment method when performing the heat treatment were changed as shown in Tables 1 and 2, respectively. The conditions when forming the cobalt plating layer were such that the total amount of nickel and cobalt (including the amount of nickel in the underlying nickel plating layer) was the amount shown in Tables 1 and 2. The results are shown in Tables 1 and 2. For Example 2, the Co concentration gradient ΔP Co , Ni concentration gradient ΔP Ni , Ni concentration P Ni (D Ni_0.5% ), Co concentration P Co (D Ni_0.5% ), and Fe concentration P Fe (D Ni_0.5% ) is measured by high-frequency glow discharge optical emission spectrometry for a surface-treated steel sheet.

[0103] Comparative Examples 1 to 3 Surface-treated steel sheets were prepared and evaluated in the same manner as in Example 1, except that the amount of nickel deposited when forming the nickel plating layer was changed as shown in Table 1, that a cobalt plating layer was not formed, and that the heat treatment temperature and heat treatment method when performing the heat treatment were changed as shown in Tables 1 and 2. The results are shown in Table 1. In Comparative Examples 1 to 3, a cobalt plating layer was not formed, and therefore cobalt was not detected in the measurement by fluorescent X-ray analysis. However, in the measurement by high-frequency glow discharge optical emission spectrometry, the emission wavelength of cobalt is close to the emission wavelength of nickel and iron, so cobalt may be detected in the measurement result. However, since the surface-treated steel sheets of Comparative Examples 1 to 3 do not form a cobalt plating layer, it is clear that they do not contain cobalt. Therefore, in calculating the concentration of each element based on the intensity ratio obtained by high-frequency glow discharge optical emission spectrometry, the Co concentration P calculated based on the Co intensity of the measurement result was used. Co (D Ni_0.5%) was very small (less than 2 mass%), so it was determined that no cobalt was contained. Based on the ratio of Ni intensity and Fe intensity when the sum of Ni intensity and Fe intensity was taken as 100%, the Ni concentration P Ni (D Ni_0.5% ) and Fe concentration P Fe (D Ni_0.5% In Comparative Examples 1 to 3, the ratio R Fe / Co No calculation was performed.

[0104] Comparative Example 4 Surface-treated steel sheets were produced in the same manner as in Example 1, except that a cobalt plating layer was formed directly on the steel sheet without forming a nickel plating layer, that the conditions for forming the cobalt plating layer were changed as shown in Table 1, and that no heat treatment was performed, and were evaluated in the same manner. The conditions for forming the cobalt plating layer were such that the total amount of nickel and cobalt (including the amount of nickel in the underlying nickel plating layer) was the amount shown in Table 1. The results are shown in Table 1. For Comparative Example 4, the corrosion current density value was clearly large, and it was confirmed that when used as a battery container, the corrosion resistance to the electrolyte would be poor, so the contact resistance value was not measured.

[0105] Comparative Examples 5 to 12 Surface-treated steel sheets were produced and evaluated in the same manner as in Example 1, except that the amount of nickel deposited when forming the nickel plating layer, the conditions when forming the cobalt plating layer, and the heat treatment temperature and heat treatment method when performing the heat treatment were changed as shown in Table 1. The conditions when forming the cobalt plating layer were such that the total amount of nickel and cobalt (including the amount of nickel in the underlying nickel plating layer) was the amount shown in Table 1. The results are shown in Table 1. For Comparative Examples 5 to 12, the corrosion current density values ​​were clearly large, and it was confirmed that when used as a battery container, the corrosion resistance to the electrolyte would be poor, so the contact resistance values ​​were not measured.

[0106] [Table 1]

[0107] [Table 2]

[0108] As shown in Tables 1 and 2, the depth position D Co_MAX From the depth position D Co_15% Co concentration gradient ΔP Co The surface-treated steel sheet with a nickel-cobalt-iron diffusion layer with a controlled nickel content of 33 mass% / 0.1 μm or less had a corrosion current density of 0.03 mA / cm 2 Less than or equal to 0.002 mA / cm 2 Since the contact resistance after aging was 8 mΩ or less, it was confirmed that the battery had excellent resistance to elution and that the deterioration of the battery characteristics after aging was suppressed (Examples 1 to 5 In addition, in Examples 1 to 5 Regarding the depth position D Ni_MAX From the depth position D Ni_15% Ni concentration gradient ΔP Ni When the Ni concentration gradient ΔP of Example 1 was measured, Ni is 36.6 mass% / μm, Example 2 is 39.8 mass% / μm, Example 3 is 32.5 mass% / μm, Example 4 is 21.4 mass% / μm, and Example 5 is 13.6 mass% / μm. m In addition, in Examples 1 to 5 The half-width W of the Co concentration at Co In Example 1, the thickness is 0.23 μm, in Example 2, the thickness is 0.19 μm, in Example 3, the thickness is 0.20 μm, in Example 4, the thickness is 0.25 μm, and in Example 5, the thickness is 0.53 μm. m there were.

[0109] On the other hand, as shown in Tables 1 and 2, when the nickel-cobalt-iron diffusion layer was not formed on the outermost layer, or when the Co concentration gradient ΔP CoWhen the average particle size exceeds 33 mass % / 0.1 μm, the corrosion current density becomes high, resulting in poor resistance to elution, or the contact resistance value after aging becomes high, resulting in deterioration of the battery characteristics after aging (Comparative Examples 1 to 12).

[0110] In addition, the color change due to constant temperature and humidity testing (ΔL * ) in Example 3 is the color tone change amount (ΔL * ): -0.3, in Example 4, the color change amount (ΔL * ):-0.6, and in Comparative Example 4, the color tone change (ΔL * ):-3.0, and in Comparative Example 6, the color tone change (ΔL * ):-1.4, and in Comparative Example 12, the color change (ΔL * ): -1.1, and in Examples 3 and 4, the color change due to the constant temperature and humidity test (ΔL * ) was suppressed to a low level. to 5 In this regard, as in Examples 3 and 4, the color change amount (ΔL * ) has been kept low. [Explanation of symbols]

[0111] 1, 1a…Surface-treated steel sheet 11...Steel plate 12...Nickel-cobalt-iron diffusion layer 13...Nickel plating layer 14...Cobalt plating layer 15...Iron-nickel diffusion layer

Claims

1. A steel plate, A surface-treated steel sheet comprising a nickel-cobalt-iron diffusion layer formed as a top surface layer on the steel sheet, The Ni intensity, Co intensity and Fe intensity are continuously measured from the surface side of the nickel-cobalt-iron diffusion layer toward the depth direction by high-frequency glow discharge optical emission spectrometry, and the Ni concentration, Co concentration and Fe concentration at each depth position of the nickel-cobalt-iron diffusion layer are calculated based on the Ni intensity, the Co intensity and the Fe intensity. The depth position at which the Co concentration has a maximum value is designated as D Co_MAX and the depth position D Co_MAX The depth position at which the Co concentration is 15% of the maximum value is defined as D Co_15% In this case, the depth position D Co_MAX From the depth position D Co_15% Co concentration gradient ΔP Co is 33 mass% / 0.1 μm or less, The surface-treated steel sheet has a half-value width W Co of Co concentration of 0.1 to 0.35 μm.

2. The Ni intensity, Co intensity and Fe intensity are continuously measured from the surface side of the nickel-cobalt-iron diffusion layer toward the depth direction by high-frequency glow discharge optical emission spectrometry, and the Ni concentration, Co concentration and Fe concentration at each depth position of the nickel-cobalt-iron diffusion layer are calculated based on the Ni intensity, the Co intensity and the Fe intensity. The depth position at which the Ni concentration shows the maximum value is D Ni_MAX and the depth position D Ni_MAX The depth position D is closer to the steel plate than the depth D and where the Ni concentration is 15% of the maximum value. Ni_15% In this case, the depth position D Ni_MAX From the depth position D Ni_15% Ni concentration gradient ΔP Ni The surface-treated steel sheet according to claim 1 , wherein the surface roughness is 15 mass % / μm or more.

3. The Ni intensity, Co intensity, and Fe intensity of the nickel-cobalt-iron diffusion layer are continuously measured from the surface side toward the depth direction by high-frequency glow discharge optical emission spectrometry, and the Ni concentration, Co concentration, and Fe concentration at each depth position of the nickel-cobalt-iron diffusion layer are determined based on the Ni intensity, the Co intensity, and the Fe intensity. Among the depth positions in the nickel-cobalt-iron diffusion layer where the Ni intensity is 0.5% of the maximum value, the depth position located on the surface side is defined as D. Ni_0.5% In this case, the depth position D Ni_0.5% Ni concentration P Ni (D Ni_0.5% ) is 70 mass% or less, and the Co concentration P Co (D Ni_0.5% ) is 5 mass% or more, and the Fe concentration P Fe (D Ni_0.5% 3. The surface-treated steel sheet according to claim 1, wherein the content of Cd is 15 mass % or more.

4. The depth position D Ni_0.5% In the Fe concentration P Fe (D Ni_0.5% 4. The surface-treated steel sheet according to claim 3, wherein the content of C is 30 mass % or more.

5. The depth position D Ni_0.5% In the Co concentration P Co (D Ni_0.5% 5. The surface-treated steel sheet according to claim 3, wherein the content of C is 12 mass% or more.

6. The content of Co contained in the nickel-cobalt-iron diffusion layer is 0.2 g / m 2 The surface-treated steel sheet according to any one of claims 1 to 5.

7. The content of Ni contained in the nickel-cobalt-iron diffusion layer is 0.2 to 12.5 g / m 2 The surface-treated steel sheet according to any one of claims 1 to 6,

8. The content of Ni contained in the nickel-cobalt-iron diffusion layer is 0.2 to 7.0 g / m 2 The surface-treated steel sheet according to claim 7,

9. The total content of Ni and Co contained in the nickel-cobalt-iron diffusion layer is 1.6 to 14.0 g / m 2 The surface-treated steel sheet according to any one of claims 1 to 8.

10. The total content of Ni and Co contained in the nickel-cobalt-iron diffusion layer is 1.6 to 7.5 g / m 2 The surface-treated steel sheet according to claim 9 .

11. The surface-treated steel sheet according to any one of claims 1 to 10, further comprising an iron-nickel diffusion layer between the steel sheet and the nickel-cobalt-iron diffusion layer.

12. The total content of Ni contained in the nickel-cobalt-iron diffusion layer and the iron-nickel diffusion layer is 1.0 to 12.5 g / m 2 The surface-treated steel sheet according to claim 11 .

13. The total content of Ni and Co contained in the nickel-cobalt-iron diffusion layer and the iron-nickel diffusion layer is 1.6 to 14.0 g / m 2 The surface-treated steel sheet according to claim 11 or 12,

14. A battery container comprising the surface-treated steel sheet according to any one of claims 1 to 13.

15. A battery comprising the battery container according to claim 14.

16. A method for producing the surface-treated steel sheet according to any one of claims 1 to 9, On the steel plate, a nickel content of 0.2 to 12.5 g / m 2 forming a nickel plating layer comprising: A layer of nickel plating having a cobalt content of 0.2 to 5.0 g / m 2 forming a cobalt plating layer comprising: The steel sheet on which the nickel plating layer and the cobalt plating layer are formed is subjected to a heat treatment at a temperature of 450 to 900° C., thereby obtaining a Co concentration gradient ΔP Co and forming a nickel-cobalt-iron diffusion layer having a nickel-cobalt-iron content of 33 mass % / 0.1 μm or less as an outermost layer.